2015
DOI: 10.1017/bec.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Management of Headache Triggers: Three Case Examples Illustrating a New Effective Approach (Learning to Cope with Triggers)

Abstract: The traditional approach to headache trigger management is to advise avoidance of all triggers, but we have advocated an alternative approach called 'Learning to Cope with Triggers' (LCT), in which the objective is to desensitise headache sufferers to some triggers or to build up tolerance for the triggers, using exposure techniques. A recent publication established the efficacy of this approach to trigger management. Reported here are three cases to illustrate how LCT is used in practice. Two cases were male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…In a recently completed study, LCT was found to result in a 35.9% reduction in headaches compared with a 13.2% reduction for advice to avoid all triggers (Martin et al, 2014). LCT has been illustrated in a series of three case studies (Martin, Callan, Kaur, & Gregg, 2015).…”
Section: What This Paper Addsmentioning
confidence: 99%
“…In a recently completed study, LCT was found to result in a 35.9% reduction in headaches compared with a 13.2% reduction for advice to avoid all triggers (Martin et al, 2014). LCT has been illustrated in a series of three case studies (Martin, Callan, Kaur, & Gregg, 2015).…”
Section: What This Paper Addsmentioning
confidence: 99%
“…In fact, really harmful triggers (eg, an excessive lack of sleep) should be avoided; however, exposure‐based strategies are more favorable for many other triggers (eg, stress, physical activity, and cognitive exertion). Thus, the LCT promotes flexible handling of triggers, the “behavioral management of headache triggers” or “trigger management.” Additionally, there are (5) a number of behavioral treatments that address specific psychological challenges of migraine. These are interventions that (a) advocate a regular and well‐balanced lifestyle; (b) support coping with fear of migraine attacks; and (c) support coping with a current migraine attack.…”
mentioning
confidence: 99%
“…Thus, the LCT promotes flexible handling of triggers, the "behavioral management of headache triggers" or "trigger management." 13,22 Additionally, there are (5) a number of behavioral treatments that address specific psychological challenges of migraine. These are interventions that (a) advocate a regular and well-balanced lifestyle; (b) support coping with fear of migraine attacks; and (c) support coping with a current migraine attack.…”
mentioning
confidence: 99%
“…The significance of triggers is that they have always featured in the clinical management of headache and migraine with the standard advice being to avoid triggers as a strategy for preventing headaches . In recent years this approach has been challenged, and an alternative approach developed called “Learning to Cope with Triggers” (LCT), which continues to advocate avoidance of some triggers but utilizes exposure to other triggers with the goal of desensitization to those triggers or increasing tolerance for those triggers . LCT has been compared with the traditional advice to avoid all triggers in a randomized controlled trial and has been shown to be more effective in terms of reduction in headaches and medication consumption .…”
mentioning
confidence: 99%
“…12 In recent years this approach has been challenged, [13][14][15] and an alternative approach developed called "Learning to Cope with Triggers" (LCT), which continues to advocate avoidance of some triggers but utilizes exposure to other triggers with the goal of desensitization to those triggers or increasing tolerance for those triggers. 16 LCT has been compared with the traditional advice to avoid all triggers in a randomized controlled trial and has been shown to be more effective in terms of reduction in headaches and medication consumption. 17 "Coping with triggers" is now being advocated by an increasing number of authors [18][19][20] and is included in the European Federation of Neurological Societies Guidelines on the treatment of tension-type headache.…”
mentioning
confidence: 99%